Perfil soroepidemiológico e detecção molecular de Toxoplasma gondii em Gallus gallus e Columba livia da região metropolitana de Goiânia, Goiás - Silveira Neto, Osvaldo José da (2013)
The objective of this work was to evaluate the epidemiological situation of T. gondii in domestic and synanthropic birds in the metropolitan region of Goiânia, Goiás, by means of serological and molecular tests. By using modified agglutination and indirect hemagglutination techniques, samples from 450 domestic poultry (Gallus gallus) were evaluated, of which 150 birds were free-range (subsistence conditions), 150 were laying hens and 150 were broiler fowl. Research was also carried out, using direct agglutination (MAT) and PCR, on the occurrence of T. gondii in 80 free-range hens sold in open markets and on 150 common pigeons (Columba livia) in the Goiânia region. Antibodies for the parasite were found in all types of birds investigated, and there was a statistical difference in relation to positivity (p<0.05), which ranged in ascending order, thus: broilers (4.7%), layers (11.3%) and free-range fowl (38%). As regards birds sold at fairs, positivity was high, increasing proportionally with the number of fragments tested, without differences (p>0.05) in heart or brain samples (38.75% positive in MAT and 70 % positive in PCR). There was an association between chickens found positive in the modified agglutination and PCR tests, and it was noted that the higher the titer in the serology, the greater was the chance of positivity in the PCR. The pigeons presented positivity of 22.6% in the serology and low positivity in PCR (2%), with cysts only detected in brain samples. Occurrence of T. gondii was detected in all types of birds and rearing systems analyzed. Research into T. gondii in domestic chickens and in pigeons in this work proves the importance of these birds as indicators of environmental contamination, as well as providing evidence of the potential risks that they bring to public health in the region of Goiânia, Goiás.